2011
DOI: 10.1182/blood-2011-04-347526
|View full text |Cite
|
Sign up to set email alerts
|

Human microRNA-27a* targets Prf1 and GzmB expression to regulate NK-cell cytotoxicity

Abstract: IntroductionNatural killer (NK) cells play key roles in innate and adaptive immune responses during early host defense against infectious pathogens and tumors via 2 major mechanisms: contact-dependent cytotoxicity and cytokine production for immune modulation. [1][2][3][4] Target-cell death is primarily mediated via the granule-exocytosis pathway. NK cells are armed by functional cytotoxic granules containing perforin (Prf1) and granzymes, essential effector molecules for NK-cell cytotoxicity as shown in knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 52 publications
2
93
2
2
Order By: Relevance
“…Both perforin and granzyme B have been described as targets of microRNA-dependent regulation in NK cells. [37][38][39] Further research will be required to investigate whether STAT3 interferes with the control of microRNAs in NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both perforin and granzyme B have been described as targets of microRNA-dependent regulation in NK cells. [37][38][39] Further research will be required to investigate whether STAT3 interferes with the control of microRNAs in NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have characterized mRNA targets of miRs-21-3p and -27a-5p in immune cells such as eosinophils and natural killer (NK) cells and cancers such as hepatocellular carcinoma and head and neck squamous cell carcinoma (27)(28)(29)(30). However, how miRs-21-3p and -27a-5p regulate gene expression in ECs is not known.…”
Section: Identifi Cation Of Biological Pathways Regulated Mirs-21-3p mentioning
confidence: 99%
“…crosslinking immunoprecipitation-based methods, which utilize by guest, on www.jlr.org granzymes to induce apoptosis. Recent work has shown that expression of miR-27a-5p leads to loss of cytoxicity of NK-cells through direct transcriptional repression of perforin 1 ( PRF1 ) and granzyme B ( GZMB ), suggesting miR-27a-5p as repressor of apoptosis ( 28 ).…”
Section: Identifying Mirna Targetsmentioning
confidence: 99%
“…14 Furthermore, some miRNAs, such as miR-27a-5p, miR-378 and miR-30e, perturb NK cell cytolytic activity by targeting the granule proteins granzyme B and perforin. 7,15 Finally, miR-30c-1-3p enhances NK cell cytotoxicity by targeting HMBOX1, an inhibitory transcription factor for cytokines. 16 In summary, miRNAs can modulate both the development and function of NK cells.…”
Section: Introductionmentioning
confidence: 99%